ANIMASI INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA PADA TK AL ANHAR BOJONG GEDE JAWA BARAT - Jehan Saptia Kurnia (JURNAL MITRA MANAJEMEN, 2019)
Developing reading skills from an early age ( kindergarten ) is very important in a child's life , including the preparation of subsequent children entering further education . With the expected reading ability of children to new vocabulary and can read well will thus be able to socialize well and can develop creative thinking in children .There are some things that need to be considered in determining the learning methods to motivate students to learn effectively and learning resources needed fun or interesting props and fun . The selection of instructional media using interactive animation media ( multimedia ) that contains moving pictures , sound and text, is one of the alternative media that can be used as a learning tool in the learning study aids Siwa . In this study the authors tried to make Applications Improve Student Reading Ability . Implementation and validation results showed that the application has been made fit for use as learning to improve reading skills . The use of interactive media such as computer -aided simulation and is able to provide immediate feedback so that potentially attract attention and motivate children to learn .